Green Route Biosynthesis of Shape‐Tunable ZnO Nanostructures and Their Photocatalytic Applications. Issue 34 (4th December 2017) - Phukan, Shreemoyee; Bomjen, Peto; Shripathi, Thoudinja; Rashid, Md. Harunar
Abstract: Herein, we report the synthesis of ZnO nanostructures of different morphologies via a facile and efficient wet chemical approach using flower extract as capping agent under ambient conditions. The purified samples were characterized via UV‐vis spectroscopy, photoluminescence spectroscopy, X‐ray diffractometry, electron microscopy, and thermogravimetric analysis. The diffractograms revealed that the products are pure and are well crystallized in a hexagonal wurtzite structure. The electron microscopic results confirmed that varying the concentration of flower extract, size and shape of ZnO nanostructures could be tuned. Microscopic results also clearly revealed that the flower like three dimensional morphologies of ZnO transforms gradually to spherical shape with increase in flower extract concentration. The ZnO nanostructures exhibit excellent photocatalytic activities towards the degradation of cationic dyes such as methylene blue and rhodamine B under UV light irradiation indicating that the flower extract derived ZnO architecture is a promising material for removal of pollutants from waste water. The effect of reaction parameters such as shape, size and amount of catalyst on the photocatalytic degradation of dyes were also studied. The results revealed that the maximum decolorization of dyes occur with ZnO photocatalyst at basic pH under UV light irradiation. The ZnO nanostructures are highly stable and are reusable for successive batches without losing any photocatalytic activity. Abstract : ZnO nanostructures of various morphologies have been synthesized by alkaline hydrolysis of zinc salts at ambient conditions using plant extract as shape‐directing agent. Variation of plant extract concentration results in the formation of ZnO of different morphologies. These ZnO nanostructures can be used as photocatalyst for cationic organic dyes under irradiation in UV lamp for successive batches without losing their photocatalytic activities.